Construction of Bibenzothiophenes through Oxidative C–H Cyclization with 1,3-Diynes - Chen, Jingyi; Lei, Tao; Wan, Danyang; Yang, Yudong (Synlett, 2023)
The development of concise and efficient methods to construct bithiophene derivatives is an appealing task in the fields of organic chemistry and organic functional materials. Herein, we summarize our recent efforts towards the development of catalytic oxidative C–H cyclization reactions of thiophenol derivatives with 1,3-diynes, which provides a straightforward and effective synthetic approach to both symmetrical and nonsymmetrical 3,3′-bibenzothiophenes. This work is expected to stimulate the application of catalytic oxidative C–H annulation of aromatics with 1,3-diynes for the exploitation of organic functional materials.
Keywords: oxidative cyclization; C–H functionalization; bibenzothiophenes; 1,3-diynes; heptagonal imides